Gasification of biochar from empty fruit bunch in a fluidized bed reactor - Mohd Salleh, Mohamad Amran; Kisiki, Nsamba Hussein; Mohamed Yusoff, Hamdan; Wan Ab. Karim Ghani, Wan Azlina (MDPI, 2010)
A biochar produced from empty fruit bunches (EFB) was gasified in a fluidized bed using air to determine gas yield, overall carbon conversion, gas quality, and composition as a function of temperature. The experiment was conducted in the temperature range of 500–850 °C. It was observed that biochar has the potential to replace coal as a gasification agent in power plants. Hydrogen gas from biochar was also optimized during the experiment. High temperatures favor H2 and CO formation. There was an increase of H2 over the temperature range from 500–850 °C from 5.53% to 27.97% (v/v), with a heating value of 30 kJ/g. The C conversion in the same temperature range increased from 76% to 84%. Therefore, there are great prospects for the use of biochar from EFB as an alternative fuel in power plants, as a renewable energy providing an alternative path to biofuels. Results from this work enable us to better understand syn gas production under high treatment temperatures.